GIS-Driven mineral exploration: Enhancing geological insight through aeromagnetic integration - Benyas Kawtar; Idrissi Assia; Qarbous Abdelmounim; Sassioui Slimane; Aarab Abdellatif; Lakhloufi Abdellah; Aitali Rajaa (E3S Web of Conferences)
The Rehamna Variscan massif, located in the western Moroccan Meseta, is known for its geological complexity and mining potential, requiring detailed investigation to uncover its hidden resources. This study combines spatial analysis with aeromagnetic geophysical prospecting methods, using Geographic Information Systems (GIS), which are effective for integrating spatio-temporal data and organizing research phases. The goal is to demonstrate that incorporating aeromagnetic data into GIS enhances the detection and analysis of geological structures, thus facilitating mineral prospecting. This integration identified a significant bipolar magnetic anomaly, similar to that of the Hajjar mine, indicating favorable geological structures for mineralization. It also helped map faults and other geological discontinuities, revealing new target areas for in-depth mineral exploration, particularly for precious metals. The findings highlight the effectiveness of GIS in mineral prospecting in geologically complex regions. However, interpreting the data requires expertise in geophysics and geology to improve model accuracy. This combined approach allows for more precise analysis and better planning of mining exploration efforts.